2012
DOI: 10.4049/jimmunol.1103609
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: The Role of IFN-α Receptor and MyD88 Signaling in Induction of IL-15 Expression In Vivo

Abstract: Interleukin-15 (IL-15) plays a multifaceted role in immune homeostasis, but the unreliability of IL-15 detection has stymied exploration of IL-15 regulation in vivo. To visualize IL-15 expression, we created a transgenic mouse expressing emerald-GFP (EmGFP) under IL-15 promoter control. EmGFP/IL-15 was prevalent in innate cells including dendritic cells (DCs), macrophages, and monocytes. However, DC subsets expressed varying levels of EmGFP/IL-15 with CD8+ DCs constitutively expressing EmGFP/IL-15 and CD8− DCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
84
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(93 citation statements)
references
References 23 publications
8
84
1
Order By: Relevance
“…Although IL-15 expression by DCs has been reported, the distribution of IL-15-expressing cells in the stromal cell fraction remains relatively uncharacterized in part because of low protein expression. Recently, others constructed two BAC transgenic mouse lines to track IL-15-expressing cells (13,14). However, in those mice, detection of IL-15-expressing cells was limited to hematopoietic subsets, possibly because the BAC constructs lack regulatory elements necessary for stromal cell IL-15 expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although IL-15 expression by DCs has been reported, the distribution of IL-15-expressing cells in the stromal cell fraction remains relatively uncharacterized in part because of low protein expression. Recently, others constructed two BAC transgenic mouse lines to track IL-15-expressing cells (13,14). However, in those mice, detection of IL-15-expressing cells was limited to hematopoietic subsets, possibly because the BAC constructs lack regulatory elements necessary for stromal cell IL-15 expression.…”
Section: Discussionmentioning
confidence: 99%
“…To overcome these difficulties, two independent laboratories constructed IL-15 reporter mice by introducing BAC transgenes harboring genes encoding fluorescent reporters controlled by the IL-15 promoter (13,14). By using these mice, they detected significant fluorescence signals in CD8…”
mentioning
confidence: 99%
“…22 CD8a 1 DCs also express high levels of IL-15 under steady-state conditions. 34 As IL-15 or IL-15Ra deficiency affects the survival and the numbers of DC under steady state, 35 we postulated that cross-presentation of systemically administered LM-OVA might be defective in the absence of IL-15 trans-presentation. However, our results from the NOD model and the RIP-GP model suggested that IL-15 transpresentation is not required to activate diabetogenic T cells.…”
Section: Il-15ra Is Required To Maintain Effector Cd8 1 T Cells Genermentioning
confidence: 99%
“…Accordingly, increased secretion of type I IFN or an IFN-stimulated gene signature is observed in a spectrum of autoimmune diseases correlating with increased disease severity [37]. Type I interferon may notably stimulate the survival and proliferation of CD8+ T cells and NK cells [37] either directly or via the induction of IL-15 [38]. A virus might also stimulate IL-15 induction via stimulation of Toll-ligand receptor 3 [39].…”
Section: Pathogenesismentioning
confidence: 99%